2010
DOI: 10.2478/s11536-009-0107-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma level of myeloperoxidase in children with juvenile idiopathic arthritis (a pilot study)

Abstract: AbstractTo examine the plasma levels of MPO in oligoarthritis and polyarthritis subtypes of JIA in comparison with healthy age-matched controls. Thirty-eight JIA patients (25 girls and 13 boys) aged 9.1–11.8 years and 23 healthy controls (8 girls and 15 boys) participated in the study. Twenty-one patients had oligoarthritis (8 with extended oligoarthritis) and 17 had polyarthritis (among them three were seropositive). The plasma concentration of MPO was measured by the ELISA te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Several studies have shown that increased MPO concentration is associated with an increased risk of CVD [ 27 , 28 ]. Also, studies have shown higher serum and plasma concentrations in patients with rheumatologic diseases [ 9 , 29 ]. In our study, we found higher serum levels of MPO in patients with JIA already at an early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that increased MPO concentration is associated with an increased risk of CVD [ 27 , 28 ]. Also, studies have shown higher serum and plasma concentrations in patients with rheumatologic diseases [ 9 , 29 ]. In our study, we found higher serum levels of MPO in patients with JIA already at an early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…MPO, ADMA and adiponectin have been linked to inflammation and/or oxidative stress [ 6 8 ]. Previous studies have shown that MPO levels are higher in patients with JIA compared with control groups [ 9 ]. ADMA and adiponectin have not been investigated in patients with JIA.…”
Section: Introductionmentioning
confidence: 99%
“…More, FRs directly contribute to the degradation of collagen, depolymerization of hyaluronic acid and disturbance of the synthesis of proteoglycan core proteins [ 30 ]. The hypothesis regarding the increased free radical activity characterizing JIA patients is confirmed by the increased levels of oxidative stress markers, i.e., the products of lipid or protein peroxidation, circulating in the blood of the patients, which has been demonstrated by other researchers [ 16 , 17 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 70%
“…TGF-β may additionally act as a stimulator of the inflammatory process as well as synovial hyperplasia and fibrosis [ 38 ]. The discussed cytokine stimulates the synthesis of proinflammatory cytokines, including IL-1 and TNF-α, by the cells of the synovial membrane [ 32 ]. Hence, the pathways of ECM transformation dependent on the discussed factor are not unidirectional and are related to its concentration [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children with JIA have higher plasma MPO levels than healthy. In the group of patients with the arthropathy the highest concentration of MPO is observed in children with polyarticular JIA [98,99].…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 93%